Determination of Internal Business Factors on Sales Volume: A Review of QRIS Moderation in Traditional Market Traders - Budi Ihsan; Agustia Handayani; Sri Yuli Astuti; Allan Harris (Al-Mashrof: Islamic Banking and Finance, 2025)
This study aims to analyze the effect of Capital, Discounts, and Product Prices on Sales Volume with the QRIS payment system as a moderating variable in the Pringsewu Central Market. A quantitative approach was used with data collection techniques through questionnaires administered to 30 traders at Pringsewu Central Market. With the help of Smart PLS, the results of multiple regression analysis in this study show that capital, discounts, and product prices have a significant positive partial effect on sales volume. Meanwhile, the results of Moderated Regression Analysis (MRA) show that capital and product prices with the QRIS payment system as a moderating variable do not have a significant effect on sales volume. Meanwhile, the discount variable significantly affects sales volume when moderated by the QRIS payment system. Keywords: QRIS, traditional market, sales volume, business